High Photosynthetic Rates in a Solanum pennellii Chromosome 2 QTL Is Explained by Biochemical and Photochemical Changes - Lana-Costa, Jaciara; de Oliveira Silva, Franklin Magnum; Batista-Silva, Willian; Carolino, Diego Costa; Senra, Renato Lima; Medeiros, David B.; Martins, Samuel Cordeiro Vitor; Gago, Jorge; Araújo, Wagner L.; Nunes-Nesi, Adriano (Frontiers in Plant Science, 2020)
Enhanced photosynthesis is strictly associated with to productivity and it can be accomplished by genetic approaches through identification of genetic variation. By using a Solanum pennellii introgression lines (ILs) population, it was previously verified that, under normal [CO2], IL 2-5 and 2-6 display increased photosynthetic rates by up to 20% in comparison with their parental background (M82). However, the physiological mechanisms involved in the enhanced CO2 assimilation exhibited by these lines remained unknown, precluding their use for further biotechnological applications. Thereby, here we attempted to uncover the physiological factors involved in the upregulation of photosynthesis in ILs 2-5 and 2-6 under normal [CO2] as well as under elevated [CO2]. The results provide evidence for increased biochemical capacity (higher maximum carboxylation velocity and maximum electron transport rate) in plants from IL 2-5 and 2-6, whereas the diffusive components (stomatal and mesophyll conductances) were unaltered in these ILs in comparison to M82. Our analyses revealed that the higher photosynthetic rate observed in these ILs was associated with higher levels of starch as well as total protein levels, specially increased RuBisCO content. Further analyses performed in plants under high [CO2] confirmed that biochemical properties are involved in genetic variation on chromosome 2 related to enhanced photosynthesis.